RANCANG BANGUN SISTEM INFORMASI AKADEMIK BERBASIS WEB MENGGUNAKAN CODEIGNITER 4 PADA SIT TARUNA AR RISALAH - Muhammad Arroyyan Hamel; Berta Erwin SLAM (Smart Education, 2026)
Abstract: This study aims to design and develop a web-based Academic Information System at SIT Taruna Ar Risalah Tanjungpinang to digitalize academic recording processes that were previously conducted manually using paper forms and Microsoft Excel. The system development method used in this study is the Waterfall method, which consists of requirements analysis, system design, implementation, and system testing stages. The system was developed using the CodeIgniter 4 framework with a Model-View-Controller (MVC) architecture, PHP programming language, and MySQL database. Data collection was carried out through observation and interviews, while system design used Unified Modeling Language (UML). System testing was conducted using the Black Box Testing method. The system implements Role-Based Access Control (RBAC) to manage user access rights consisting of Administrators, Principals, Teachers, and Students. The testing results indicate that all main system features function properly, including bulk attendance management, Qur’an memorization recording, Student Discipline Program evaluation, and real-time academic report presentation. The developed system is able to improve school administrative efficiency, minimize the risk of data loss, and facilitate digital monitoring of students’ academic achievements. Keywords: Academic Information System; Codeigniter 4; Waterfall; RBAC; School. Abstrak: Penelitian ini bertujuan untuk merancang dan membangun Sistem Informasi Akademik berbasis web pada SIT Taruna Ar Risalah Tanjungpinang guna mendigitalisasi proses pencatatan akademik yang sebelumnya masih dilakukan secara manual menggunakan kertas dan Microsoft Excel. Metode pengembangan sistem yang digunakan adalah metode Waterfall yang terdiri dari tahapan analisis kebutuhan, perancangan sistem, implementasi, dan pengujian sistem. Sistem dikembangkan menggunakan framework CodeIgniter 4 dengan arsitektur Model-View-Controller (MVC), bahasa pemrograman PHP, serta basis data MySQL. Pengumpulan data dilakukan melalui observasi dan wawancara, sedangkan perancangan sistem menggunakan Unified Modeling Language (UML). Pengujian sistem dilakukan menggunakan metode Black Box Testing. Sistem menerapkan Role-Based Access Control (RBAC) untuk membatasi hak akses pengguna yang terdiri dari Administrator, Kepala Sekolah, Guru, dan Siswa. Hasil pengujian menunjukkan bahwa seluruh fitur utama sistem berjalan dengan baik, meliputi pengelolaan presensi massal, pencatatan hafalan Al-Qur’an, evaluasi Program Siswa Tangguh, serta penyajian laporan akademik secara real-time. Sistem yang dibangun mampu meningkatkan efisiensi administrasi sekolah, meminimalisir risiko kehilangan data, dan mempermudah proses monitoring capaian akademik siswa secara digital. Kata Kunci: Sistem Informasi Akademik; Codeigniter 4; Waterfall; RBAC; Sekolah.